The extent of the practice of secondary school principals in the capital Sana’a of administrative creativity strategies from the point of view of principals and teachers - Al-Afad, Abdullah Ali Hadi; Al-Najjar, Abdullah Ali Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to know the extent to which secondary school principals in the capital Sana’a practice the strategies of administrative creativity, and to find out whether there are statistically significant differences between the average estimates of the study members for the principals’ practice of administrative creativity strategies, due to the variables (type, job title), and the study adopted the descriptive survey approach. The researcher used a questionnaire consisting of (28) items, which was applied to a sample of (422) individuals, including (87) principals, and (267) male and female teachers. The secondary school in the capital Sana’a for the strategies of administrative creativity according to the views of the principals and teachers working in it, and for the various fields, came with a “medium” rating, with an average of (3.30), and at the level of fields; The flexibility domain got the highest average (3.53), then the fluency domain with an average (3.41), both of them with a degree of practice (great), and the sensitivity domain for problems came in the third place, with an arithmetic mean (3.24) and a “medium” degree of practice, and finally, the originality domain with an average of (3.15) and a degree of “medium” practice. The practice of "Medium", in addition to the presence of statistically significant differences between the average estimates of the study members in the areas of fluency and flexibility due to the gender variable, and the differences in favor of males, and the presence of differences due to the job title variable, and in favor of managers. Based on the results, the study gave the following recommendations: - The necessity of holding training courses to develop the performance of secondary school principals in the capital Sana’a and all governorates of Republic on the practice of administrative creativity strategies.